The problem of depulping vital teeth during prosthesis by metal-ceramic protesis - opinions for and against - V. G. Galonsky V. G.; N. V. Tarasova; V. V. Aliamovskii; A. V. Gradoboev (LLC "Endo Press", 2020)
Relevance. The problem of preliminary depulpation of vital abutment  teeth under metal-ceramic constructions  is widely encountered in the daily practice of dentists. The decision on each clinical case is complicated by the presence of a number of arguments for each of the options for a treatment plan, namely the depulpation of the abutment teeth before prosthetics or preservation of their vitality.Aim. To study the practical aspects of the problem of pre-depulpation of vital abutment teeth during prosthetics with non-removable metal-ceramic dentures.Materials and methods. A two-stage survey of 335 dentists, students of advanced training courses at the Department of Dentistry IPO KrasGMU them. prof. V.F. Voyno-Yasenetsky (Krasnoyarsk) and analysis of the received questionnaires.Results. As a result of the research, it was revealed that the expediency of preserving abutment teeth vital for prosthetics with non-removable metal-ceramic dentures has 5 positive sides (two of which are more fnancial and marketing than medical) than nine negative sides. It is diametrically opposed to the expediency of preliminary depulpation of vital abutment teeth before prosthetics with non-removable metal-ceramic dentures, which has 9 positive and 7 negative sides.Conclusions. Thus, because of the  survey, we can conclude  that among dental  specialists,  the most preferable was  the preliminary depulpation of vital abutment teeth for metal-ceramic constructions, especially with increasing professional experience, which is also traced by the number of positive and negative sides of each treatment approaches.